Generation Z involvement, cultural identity, and purchase intention in the homestay context: Evidence from tea-culture homestays - Qing Zhang; Huazhen Sun; Qiuyan Lin; Weifeng Guo (PLoS ONE, 2026)
This study examines how Generation Z involvement influences purchase intention for tea-culture homestays and whether cultural identity mediates this relationship. The attention of generation Z consumers to the cultural connotation of homestay is increasing, which has an impact on the subsequent development and continuous operation of homestay. This paper applies the theory of involvement and cultural identity, takes generation Z consumers as the research group, explores the influence of generation Z consumers’ involvement and cultural identity on their purchase intention, and studies the mediating role of cultural identity in this process, thus constructs a model of the relationship between generation Z consumers’ involvement, cultural identity and the influence of purchase intention of tea culture homestay, and applies SPSS24.0 and AMOS24.0 to analyze the data for empirical verification. data analysis for empirical verification. It is found that: (1) the degree of involvement of the generation Z of consumers has a significant positive effect on the cultural identity and purchase intention of tea culture homestay; (2) the cultural identity of the generation Z of consumers on tea culture homestay can positively affect the purchase intention of the consumers; (3) there is a partially mediating effect of the cultural identity in the degree of involvement of the generation Z of consumers and the purchase intention of the consumers. Finally, this paper puts forward relevant suggestions for the research conclusions.